Interventions that address institutional child maltreatment: evidence and gap map. Issue 1 (9th March 2021) - Finch, Meghan; Featherston, Rebecca; Chakraborty, Sangita; Bjørndal, Ludvig; Mildon, Robyn; Albers, Bianca; Fiennes, Caroline; Taylor, David J. A.; Schachtman, Rebecca; Yang, Taoran; Shlonsky, Aron
Abstract: Background: Child maltreatment has serious short and long‐term negative impacts for those experiencing it. Child maltreatment occurring in institutional settings has recently received substantial attention. However, evidence about the effectiveness of interventions that prevent, disclose, respond to, or treat maltreatment that has occurred in these environments is fragmented and can be difficult to access. This evidence and gap map (EGM) collates this research evidence. It was developed as a resource for stakeholders operating in the child health, welfare and protection sectors, including practitioners, organisational leaders, policy developers and researchers, wanting to access high quality evidence on interventions addressing institutional child maltreatment. Objectives: The objectives of this EGM were twofold: (a) To provide a structured and accessible collection of existing evidence from finalised and ongoing overviews of systematic reviews, systematic reviews and effectiveness studies of interventions addressing institutional child maltreatment—for those who work to fund, develop, implement and evaluate interventions aimed at ensuring children's safety in institutional settings; (b) to identify gaps in the available evidence on interventions addressing institutional child maltreatment—thereby helping to inform the research agendas of funders and other organisations. Search Methods: A comprehensive search strategy identified relevant studies from published and grey literature, comprising: (1) 10 electronic academic databases; (2) five trial and systematic review registries; (3) nine organisational websites; (4) websites and reference lists of inquiry reports associated with seven international inquiries into child abuse and (4) the lists of included studies within systematic reviews identified by the search strategy. Members of this EGM's Subject Matter Experts group were also invited to forward relevant unpublished studies or grey literature. Selection Criteria: The selection criteria were developed to identify finalised and ongoing overviews of reviews, systematic reviews and primary studies that reported on the effectiveness of interventions addressing child maltreatment (including sexual abuse, physical abuse, neglect and emotional abuse) within institutional settings. Eligible effectiveness study designs included: randomised controlled trials (RCTs), nonrandomised trials, controlled before‐and‐after studies and quasi‐experimental studies. Reviews were eligible if they reported a systematic literature search strategy. Data Collection and Analysis: All screening, data extraction, coding and critical appraisals were undertaken by two or more reviewers working independently, with discrepancies resolved via consensus or by a third reviewer. The titles and abstracts of studies identified by the search strategy were screened, and each full text of potentially relevant studies was further assessed for inclusion. Key data were extracted from all included studies and reviews. This included information about: publication details (e.g., year, author, country), inclusion/exclusion criteria (for reviews), study design, institutional setting, target population, type of maltreatment, intervention type and outcomes. Critical appraisal of included systematic reviews was achieved using the AMSTAR 2 tool, and completed RCTs were assessed using the updated Cochrane Risk of Bias 2.0 tool. Main Results: Number of studies The electronic database search yielded 6318 citations, and a further 2375 records were identified from additional sources. Following deduplication and title/abstract screening, 256 studies remained for full text review. A total of 73 eligible studies (reported across 84 publications) met the inclusion criteria, including: 11 systematic reviews (plus, one update); 62 primary studies (including, three protocols for primary studies). Study characteristics The studies were conducted across 18 countries, however more than half (52%) were undertaken in the United States. Overall, most studies evaluated curriculum‐based interventions delivered in educational settings, primarily aimed at the prevention of sexual abuse. Institutional setting: Most studies evaluated interventions in school or early learning environments ( n  = 8 systematic reviews; n  = 58 primary studies). Far fewer studies examined other organisational settings. Out of home care (including foster care, residential care and orphanages), and social service organisations servicing children were minimally represented. No studies were identified where the primary setting was sports clubs, churches/religious organisations, summer/vacation camps, detention centres/juvenile justice settings, or primary/secondary health care facilities. Target population: Most interventions targeted children rather than adults ( n  = 7 systematic reviews; n  = 47 primary studies) from the general population. Fewer studies included populations known to be at an increased risk, or those already exposed to maltreatment. Just over a third of the primary studies conducted an analysis to ascertain differences in the effect of an intervention between the genders. Intervention type: Prevention interventions were the most studied ( n  = 5 systematic reviews; n  = 57 primary studies), with additional studies including prevention approaches alongside other intervention types. Fewer studies evaluated interventions targeting disclosure, institutional responses, or treatment interventions. Type of maltreatment: The vast majority of the studies assessed interventions solely addressing the sexual abuse of children ( n  = 8 systematic reviews; n  = 45 primary studies). The remaining studies addressed other forms of maltreatment, including physical and emotional abuse, or neglect, either in combination or as a sole focus. Outcomes: Primary reported outcomes reflected the bias toward child targeted interventions. Outcome measures captured child wellbeing and knowledge outcomes, including measures of mental health, children's knowledge retention and/or self‐protective skills. Measures of maltreatment disclosure or maltreatment occurrence/reoccurrence were less common, and all other outcome categories included in the EGM were minimally or not reported. A third of studies reported on some measure of implementation. Study quality The overall quality of the studies was low to moderate. Most systematic reviews were low‐quality ( n  = 10), with only one high quality review (and update) identified. Most completed RCTs had some concerns relating to the risk of bias ( n  = 30), and the remainder were considered to be at a high risk of bias ( n  = 19). Authors' Conclusions: This EGM has highlighted a substantial need for more high quality studies that evaluate interventions across a broader range of institutional contexts and maltreatment types. The current evidence base does not represent countries with large populations and the greatest incidence of child maltreatment. Few studies focussed on perpetrators or the organisational environment. Further evidence gaps were identified for interventions relating to disclosure, organisational responses and treatment, and few studies assessed interventions targeting perpetrators' maltreatment behaviours, recidivism or desistence. Future studies should also include measure of programme implementation.